2007
DOI: 10.1099/vir.0.83050-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel virus isolated from the aphid Brevicoryne brassicae with similarity to Hymenoptera picorna-like viruses

Abstract: A novel virus, Brevicoryne brassicae virus (BrBV), has been identified in the cabbage aphid using a method based on the random amplification of encapsidated RNA. The complete sequence of the RNA genome of BrBV has been determined. The positive-strand genomic RNA is 10 161 nt, excluding the 39 poly(A) tail, and contains a single open reading frame (positions 793-9744) encoding a putative polyprotein of 2983 aa. The N-terminal part of the polyprotein shows similarity with the structural proteins of iflaviruses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…Previously, some members of Iflavirus don't appear to be lethal to their hosts, such as Kakugo virus (Fujiyuki et al, 2009) and Brevicoryne brassicae virus (Ryabov, 2007). And, some members of Iflavirus are known to be harmful to their hosts by lead to developmental problems and host mortality (van Oers, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, some members of Iflavirus don't appear to be lethal to their hosts, such as Kakugo virus (Fujiyuki et al, 2009) and Brevicoryne brassicae virus (Ryabov, 2007). And, some members of Iflavirus are known to be harmful to their hosts by lead to developmental problems and host mortality (van Oers, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Some previously identified aphid-infecting viruses were detected in only a proportion of the aphids in a colony (Ryabov, 2007(Ryabov, , 2009. To test the frequency of virusinfected aphids in the M. euphorbiae colony, randomly selected single adult aphids were tested for the presence of the virus.…”
Section: Identification Of a Virus Genome In The Potato Aphid Transcrmentioning
confidence: 99%
“…These include two DNA viruses, Myzus persicae densovirus (MpDNV) (van Munster et al, 2003b) and Dysaphis plantaginea densovirus (DplDNV) (Ryabov et al, 2009), and five RNA viruses, aphid lethal paralysis virus (ALPV) (van Munster et al, 2002), Rhopalosiphum padi virus (Moon et al, 1998), Acyrthosiphon pisum virus (van der Wilk et al, 1997), Brevicoryne brassicae virus (Ryabov, 2007) and rosy apple aphid virus (RAAV) (Ryabov et al, 2009). While these aphid DNA viruses are around 5 kb in size the RNA viruses are larger, around 10 kb in size.…”
Section: Introductionmentioning
confidence: 99%
“…Several viruses of aphids have been characterized, including Myzus persicae densovirus (10); aphid lethal paralysis virus (11) and Rhopalosiphum padi virus (RhPV) (12), both members of the family Dicistroviridae; an iflavirus Brevicoryne brassicae virus (13); and the unclassified Acyrthosiphon pisum virus (APV) (14). Relatively little is known about the effect of these virus infections on aphid physiology; however, a recent study reported a change in olfactory behavior in response to RhPV infection (15).…”
mentioning
confidence: 99%